2020
DOI: 10.31234/osf.io/jbc9d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is it Ethical to Use Mechanical Turk for Behavioral Research? Relevant Data from a Representative Survey of MTurk Participants and Wages

Abstract: To understand human behavior, social scientists need people and data. In the last decade, Amazon’s Mechanical Turk (MTurk) emerged as a flexible, affordable, and reliable source of human participants and was widely adopted by academics. Yet despite MTurk’s utility, some have questioned whether researchers should continue using the platform on ethical grounds. The brunt of their concern is that people on MTurk are financially insecure, subjected to abuse, and earning inhumane wages. We investigated these issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 23 publications
4
62
0
Order By: Relevance
“…Dennis et al (2019) found that this new surge of low-quality workers is characterized by worker IP addresses that can be traced to a certain type of Internet service provider (ISP) known as virtual private servers. Furthermore, there are serious suspicions that these accounts are operated by people from outside the United States, mainly from India (Moss & Litman, 2018) and Venezuela (Kennedy et al, 2019). Therefore, participation in this study was limited to U.S. workers only and applied a newly designed tool to flag MTurk workers whose IP address was suspicious of malicious activity and/or traced to a non-U.S. location (Prims et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Dennis et al (2019) found that this new surge of low-quality workers is characterized by worker IP addresses that can be traced to a certain type of Internet service provider (ISP) known as virtual private servers. Furthermore, there are serious suspicions that these accounts are operated by people from outside the United States, mainly from India (Moss & Litman, 2018) and Venezuela (Kennedy et al, 2019). Therefore, participation in this study was limited to U.S. workers only and applied a newly designed tool to flag MTurk workers whose IP address was suspicious of malicious activity and/or traced to a non-U.S. location (Prims et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in April 2019 from American participants (N = 1077, 50.60% female, M age = 37.39 years, SD age = 11.42 years) who were recruited via Amazon's Mechanical Turk, which is considered a reliable source to obtain research participants in the United States (Buhrmester et al, 2011;Paolacci and Chandler, 2014;Huff and Tingley, 2015). Recent analysis also showed that the financial situation of MTurk participants mirrors that of the United States and that respondents do not find requesters abusive (Moss et al, 2020). Some concerns have arisen, however, due to non-United States residents trying to access the surveys intended for United States residents only.…”
Section: Participantsmentioning
confidence: 99%
“…Recent concerns were raised about the integrity of the data from MTurk (Litman, 2018), suggesting that that “bots” (i.e., automated fake accounts) were being used to answer surveys with fake data. This issue was shown to be rare to non-existent in a recent analysis (Moss & Litman, 2018). Instead, cultural and linguistic barriers were found to drive poor responses.…”
Section: General Methodsmentioning
confidence: 96%